Islamic Character Building Based on Diniyah Education at Senior High School in Banda Aceh - Mumtazul Fikri (STAI Hubbulwathan Duri, 2023)
Character building is a critical element in education. The Banda Aceh Municipal Government launched the Diniyah Education program to build adolescent character at the Public Senior High School level. This study aims to explore information about implementing the Diniyah Education program and the problems in implementing the Diniyah Education program at public senior high schools in Banda Aceh. This research is naturalistic qualitative research with phenomenological methods. The subjects of this study include six diniyah teachers, three principals and nine students. The subject of this research was chosen by purposive sampling, divided into three Senior High Schools in Banda Aceh. Data collection techniques are done through semi-structured interviews, direct observation and documentation. While the interview was conducted with diniyah teachers, principals and students, direct observations were made on implementing diniyah education at the three high schools above. The results showed that, first, the management of Diniyah Education was going well. It was evident from the following facts, recruitment of teachers professionally; a reward that is appropriate for the teacher; the use of learning methods and media according to the age of students; the selection of learning resources which are suitable for the program purpose such as the Jami' Jawami' book. Second, problems of the program include miscommunication of duties and responsibilities between diniyah teachers and schoolteachers, lack of teaching material resources about Diniyah Education, parental involvement problems, and the absence of sustainability program policies in universities. The implication of this research is to provide recommendations to the Government of Banda Aceh in order to continue and develop the diniyah education program as the spearhead of students' Islamic character building. There need to be binding regulations for the program's sustainability at the tertiary level and curriculum adjustments that are applicable and progressive according to the development of the technological age.